Pengaruh Penggunaan Media Batang Perkalian Terhadap Pemahaman Konsep Perkalian Matematika Siswa Kelas IV SDN 2 Lawe Hijo Kabupaten Aceh Tenggara - Cut Maslina Mutia; Sahkholid Nasution; Riris Nurkholidah Rambe (LPPM Politeknik Pratama, 2023)
The purpose of this study was to determine the effect of the use of multiplication bar media on the understanding of the concept of mathematical multiplication of fourth grade students of SDN 2 Lawe Hijo, Southeast Aceh Regency. The type of research used is quantitative with quasi experimental method. The research design used was Pretest-Posttest Control Group Design. Therefore, the population used was all grade IV students of SDN 2 Lawe Hijo totaling 56 students consisting of 2 classes, namely experimental and control classes. Sampling using random sampling technique so that class IVA was selected as the experimental class totaling 28 people and class IVB as the control class totaling 28 people. The study aims to determine the effect of understanding the concept of multiplication of mathematics students who are taught by using multiplication bar media and students who are taught using conventional learning models. Based on research that has been conducted in class IV SDN 2 Lawe Hijo, shows a significant effect of the application of multiplication bar media on the understanding of the concept of multiplication in mathematics subjects. This can be seen based on the average score obtained by students in the experimental class better than the control class 78.39>71.61. Based on the results of the t-test using SPSS, the significance value (2-tailed) is 0.000 <0.05, so HO is rejected and Ha is accepted. Therefore, it can be concluded that there is an effect of using the multiplication bar media on the understanding of the concept of multiplication of mathematics of fourth grade students of SDN 2 Lawe Hijo, Southeast Aceh Regency, so that the multiplication bar media can be used by teachers in improving students' understanding of the concept of multiplication.